Investigation of food grain drying with pulsating air flows - Dias, SRS; Futata, FPL; Carvalho, J. A.; Couto, H. S.; Ferreira, M. A. (Elsevier B.V., 2004)
In this article we investigate experimentally the potential of using pulsating flows for drying of food grains. A Rijke type oscillator with an electrical heater was used to dry batches of soybean grains. Drying temperatures were 60 degreesC. We observed a decrease on the drying time for pulsating flows when compared with the conventional non-pulsating regime. This decrease depended on sample initial moisture content and weight, and on final sample moisture content. (C) 2004 Elsevier B.V. Ltd.